Ticks (Acarina: Ixodida) infesting five reptile species in Sri Lanka with sixteen new host records - Liyanaarachchi, Dilrukshi R.; Rajakaruna, Rupika S.; Dikkumbura, Anil W.; Silva, Anslem De; Rajapakse, R.p.v. Jayantha (Zootaxa, 2015)
The first study on ticks on reptiles of Sri Lanka dates back to Seneviratna (1965) who reported ticks from five reptiles. Later studies were either limited to one reptile (Fernando & Fernando 2012), or captive animals in zoos (Fernando & Randeniaya 2009) and household pets (Nathanael et al. 2004). According to the current classification (Guglielmone et al. 2010), all the tick species previously recorded on reptiles belong to five species of Amblyomma: A. clypeolatum Neumann, A. gervaisi (Lucas), A. pattoni (Neumann), A. trimaculatum (Lucas) and A. varanense (Supino). Some of the species listed by Seneviratna (1965) were either synonyms or invalid in respect to the present classification. For example Amblyomma laeve sensu Warburton (1910) is a junior synonym of A. pattoni and A. gervaisii var. lucasi is considered a junior synonym of A. varanense (Guglielmone et al. 2010; D. Apanaskevich pers. comm.).